The Pedagogy of Musical Creation: classrooms and creative workshops (Tabanque. Revista Pedagógica, 2018)
Promoting the sound and musical creation of children's age is the goal of the Pedagogy of Musical Creation (PMC), whose purpose is not to get musical achievements for itself but in terms of curiosity for sound. This article is intended to put together diverse experiences of research and educational application of participating work in the classroom; propose experiences about the importance of the origin of the creative sound freedom and integrate different pedagogical practices in a harmonic way for a greater emotional development and conscious of the musical sense.
Keywords: Pedagogy of musical creation; musical awakening; creativity; children's age; teacher training